Internationalised constitution making and state formation - Seidel, Katrin, 1976- author. Link
1 online resource.
Keywords: "This book presents an in-depth and nuanced interdisciplinary and comparative analysis of (post-)conflict constitution-making in South Sudan and Somaliland, exploring the ways in which the two emerging states negotiate statehood in a globalised world. It critically examines the transfer of international constitution-making models as part of international rule of law promotion frameworks. Specific emphasis is placed on the socio-cultural translation dynamics of these models in conflict settings. The comparative study delves into the tensions between state sovereignty and international interventions, examining whether international constitution-making involvement fosters the production of societal consensus, or, inadvertently impedes efforts to achieve stability and peace. By focusing on constitutional law-making, the work sheds light on how normative ideas are transformed in negotiations and opens up new analytical avenues for re-thinking conventional constitution-making practices. It critically reconsiders the assumption that every emerging state requires a written constitution, alongside the state-centred notion of sovereignty underpinning this paradigm. Additionally, the study addresses the power and knowledge hierarchies inherent in international interventions, providing empirical data from post-conflict African contexts. The book will be of interest to academics, researchers and policy-makers working in the areas of Comparative Public Law, Constitutionalism, Sociology of Law, Anthropology, Legal Geography, Development Studies and African Studies"--